2011
DOI: 10.1093/ndt/gfr419
|View full text |Cite
|
Sign up to set email alerts
|

Two novel homozygous SLC2A9 mutations cause renal hypouricemia type 2

Abstract: This is the second report of renal hypouricemia caused by homozygous GLUT9 mutations. Our findings confirm the pivotal role of GLUT9 in UA transport and highlight the similarities and differences between RHUC1 and RHUC2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 29 publications
4
52
0
Order By: Relevance
“…Loss of function of GLUT9 results in hypouricemia, presumably as a consequence of both a reduced release of urate from the liver and poor reabsorption from the urine in the kidney. [186][187][188][189][190][191][192] Elevated levels of plasma urate have also been associated with hypertension, gout, and metabolic disease. A number of genome-wide association studies have identif ied polymorphisms in the hSLC2A9 gene.…”
Section: Glut2: Fanconi-bickel Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Loss of function of GLUT9 results in hypouricemia, presumably as a consequence of both a reduced release of urate from the liver and poor reabsorption from the urine in the kidney. [186][187][188][189][190][191][192] Elevated levels of plasma urate have also been associated with hypertension, gout, and metabolic disease. A number of genome-wide association studies have identif ied polymorphisms in the hSLC2A9 gene.…”
Section: Glut2: Fanconi-bickel Syndromementioning
confidence: 99%
“…However, to date, few, if any, single nucleotide polymorphisms have been demonstrated to have direct effects on the function of the protein when it is expressed in vitro. [187][188][189][190][191][192] It is more likely that such mutations have subtle effects on levels of expression or interactions with other proteins in the cell.…”
Section: Glut2: Fanconi-bickel Syndromementioning
confidence: 99%
“…Mutations in URAT1 and SCL2A9 result in decreased reabsorption in the proximal tubule. This results in hyperuricosuria along with low or normal serum uric acid levels (7)(8)(9). Similar mechanisms may contribute to idiopathic uric acid nephrolithiasis.…”
Section: Discussionmentioning
confidence: 98%
“…2 ). Interestingly, the Arg171 residue has been previously reported by Dinour et al [9] to be substituted by a Cys residue in 3 siblings, born of consanguineous Israeli-Arab parents, with RHUC2 and without complications. In vitro functional expression studies showed that the p.Arg171Cys mutant protein had significantly reduced UA transport activity (16% of control values).…”
Section: Case Reportmentioning
confidence: 90%
“…In vitro functional expression studies showed that the p.Arg171Cys mutant protein had significantly reduced UA transport activity (16% of control values). Furthermore, homology modelling indicated that the mutation occurred in the inner channel that expels UA from the cytoplasmic to extracellular regions [9] .…”
Section: Case Reportmentioning
confidence: 99%